2012
DOI: 10.1148/rg.322105761
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Lesions with High Signal Intensity on T1-weighted MR Images: Differential Diagnosis

Abstract: Various substances, including methemoglobin, melanin, lipid, protein, calcium, iron, copper, and manganese, are responsible for the intrinsically high signal intensity observed in intracranial lesions at T1-weighted magnetic resonance (MR) imaging. Many of these substances have physical properties that lead to other specific imaging features as well. For example, lipid-containing lesions frequently produce chemical shift artifact, and some melanin-containing lesions exhibit a combination of high signal intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
111
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(115 citation statements)
references
References 64 publications
0
111
0
4
Order By: Relevance
“…The absence of corresponding longitudinal findings in the right hemisphere may be a result of lower sensitivity in longitudinal studies and/or because the changes in CFS occurred soon after onset (before the first scan) and did not progress appreciably thereafter. The increased T2w signal intensities suggest possible decreased blood volume in these regions 31. Indeed, previous studies have found decreased regional cerebral blood flow in frontal and temporal lobes32 and decreased frontal oxygenation33 in patients with CFS.…”
Section: Discussionmentioning
confidence: 90%
“…The absence of corresponding longitudinal findings in the right hemisphere may be a result of lower sensitivity in longitudinal studies and/or because the changes in CFS occurred soon after onset (before the first scan) and did not progress appreciably thereafter. The increased T2w signal intensities suggest possible decreased blood volume in these regions 31. Indeed, previous studies have found decreased regional cerebral blood flow in frontal and temporal lobes32 and decreased frontal oxygenation33 in patients with CFS.…”
Section: Discussionmentioning
confidence: 90%
“…1 In the present case, T1-and T2-weighted images showed a hyperintense area in the anterior part of the CS that was considered a subacute thrombus. 16 The fact that the patients experienced left pulsative tinnitus 2 weeks before presenting with exophthalmos and chemosis may indicate that the shunt flowed into the CS and the SOV first, causing left-sided tinnitus (Fig. 4A), followed by obstruction of the drainage into CS, causing drainage into the SOV with subsequent resolution of tinnitus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The T1-shortening effect of iron is seldom used for the quantitative analysis of iron; instead, it is used to qualitatively check for the presence of iron. Subacute hemorrhage and melanin are typically identified by the presence of hyperintensity on T1WI [8]. The hyperintensity seen in subacute hemorrhage on T1WI is due to methemoglobin, which contains Fe 3+ .…”
Section: Ironmentioning
confidence: 99%
“…The signal intensity of melanin is related to the binding of melanin to paramagnetic metals such as Cu 2+ , Fe 3+ , Zn 2+ , and Mn 2+ ; however, it shows a particularly strong affinity for Fe 3+ which affects the signal intensity of melanin on T1WI [84,85]. Melanin appears in the brain as neuromelanin [86] and in the presence of metastatic melanoma, primary diffuse meningeal melanomatosis, neurocutaneous melanosis, and Aspergillus infection [8]. The location and extent of a region of high signal intensity on T1WI are useful diagnostic findings.…”
Section: Ironmentioning
confidence: 99%